2011
DOI: 10.1111/j.1447-0756.2010.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide is an antiapoptotic factor for human granulosa luteinized cells with impact on the results of COH/IVF in women undergoing IVF program

Abstract: Human granulosa luteinized cells are a local source of ANP in the preovulatory human follicle, which acts as a survival factor through cGMP signaling, and its levels in follicular fluids are positively associated with the number of punctured follicles, isolated oocytes and their fertilizability in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Atrial natriuretic peptide (ANP), a member of the natriuretic peptide family, is mainly secreted by atrial myocytes, which plays essential roles in regulating blood pressure, the salt and water balance and body fluid homeostasis based on its pharmacological functions in natriuresis and diuresis. 26 In addition to atrial myocytes, ANP has also been found in ovarian oocytes, 27 granulosa cells 28 and the corpus luteum. 29 Ovary-derived ANP can regulate ovarian functions, such as follicular growth and hormone production, through autocrine or paracrine manner.…”
mentioning
confidence: 99%
“…Atrial natriuretic peptide (ANP), a member of the natriuretic peptide family, is mainly secreted by atrial myocytes, which plays essential roles in regulating blood pressure, the salt and water balance and body fluid homeostasis based on its pharmacological functions in natriuresis and diuresis. 26 In addition to atrial myocytes, ANP has also been found in ovarian oocytes, 27 granulosa cells 28 and the corpus luteum. 29 Ovary-derived ANP can regulate ovarian functions, such as follicular growth and hormone production, through autocrine or paracrine manner.…”
mentioning
confidence: 99%
“…It seems evident from these findings that GCs produce the ANP proform, but not thmeans by which cleavage of the active form can be performed. Interestingly, as previous studies have provided strong evidence showing that human granulosa luteinised cells (GLCs) do express active ANP ligand (Ivanova et al 2003, Dineva et al 2011, this therefore could suggest that the mechanism for the cleavage of NPPA may not occur in GCs until ovulation when luteinisation has occurred. Although this has not been investigated here, it is tempting to speculate that the presence of NPRA on GCs may mean that, in the in vivo scenario, neighbouring TCs are able to induce signal transduction by the processing of active ANP, but this also remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported in various compartments of the ovary, including follicular fluid, theca cells (TCs), granulosa cells (GCs), the oocyte and the corpus luteum, and this suggests they may have important roles in ovarian function. They have been linked to the regulation of follicular atresia, oocyte maturation and ovarian steroidogenesis (Dineva et al 2011). NP responsiveness in follicular somatic compartments continues to be an important area of research, especially in humans or a suitable model, monovulatory species.…”
Section: Introductionmentioning
confidence: 99%